2023
DOI: 10.1007/s13167-023-00321-9
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the effect of gut microbiota on allergic conjunctivitis risk is instrumental for predictive, preventive, and personalized medicine: a Mendelian randomization analysis

Abstract: Background Allergic conjunctivitis is an ocular immune disease which affects the conjunctiva, eyelids, and cornea. Growing evidence implicates the gut microbiota in balancing and modulating immunity response, and in the pathogenesis of allergic disease. As a result, gut microbial imbalance could be a useful indicator for allergic conjunctivitis. From the perspective of predictive, preventive, and personalized medicine (PPPM), clarifying the role of gut microbial imbalance in the development of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Moreover, the non-reversibility of heredity in MR analysis is advantageous in addressing concerns related to reverse causation interference ( Xu Q. et al, 2022 ). Although the MR method has been employed in several studies to examine the potential causal relationship between gut microbiota and different diseases ( Li et al, 2022 ; Liu et al, 2023 ; Long et al, 2023 ), there is currently limited evidence regarding the causal association between gut microbiota and PBC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the non-reversibility of heredity in MR analysis is advantageous in addressing concerns related to reverse causation interference ( Xu Q. et al, 2022 ). Although the MR method has been employed in several studies to examine the potential causal relationship between gut microbiota and different diseases ( Li et al, 2022 ; Liu et al, 2023 ; Long et al, 2023 ), there is currently limited evidence regarding the causal association between gut microbiota and PBC.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be explained with the results of Liu et al who found an increased risk of allergic conjunctivitis, resulting from decreased level of Catenibacterium . 76 Children with allergic conjunctivitis have a 2.35-fold higher incidence and risk of myopia compared with children without allergic conjunctivitis. 77 Nonetheless, there is limited research on Catenibacterium in relation to the eye.…”
Section: Discussionmentioning
confidence: 99%
“…Senegalimassilia is a genus of actinobacterial strains that are Gram-positive, anaerobic, and coccobacilli-shaped ( Han et al, 2020 ). The genus Senegalimassilia was found to be a protective factor for various diseases, including hypertension ( Li et al, 2023b ), allergic conjunctivitis ( Liu et al, 2023 ). Based on our findings, this could potentially provide a strategy for extracting this bacterium from fecal samples in the future to prevent a specific disease.…”
Section: Discussionmentioning
confidence: 99%